Plasma concentration of fibronectin is decreased in patients with hypertrophic cardiomyopathy - Fucikova, Alena; Lenco, Juraj; Tambor, Vojtech; Rehulkova, Helena; Pudil, Radek; Stulik, Jiri (Clinica chimica acta, 2016)
OBJECTIVES: To confirm the initial iTRAQ-based proteomic findings related to the plasma fibronectin level and hypertrophic cardiomyopathy using an antibody-based assay. METHODS: The iTRAQ technique was used for the discovery proteomic analysis of the pooled plasma samples. The ELISA was used for verification of fibronectin plasma concentration in individual samples. Additional five related plasma proteins were assessed: matrix metalloproteinase 2, matrix metalloproteinase 9, tissue inhibitor of metalloproteinase 1, tissue inhibitor of metalloproteinase 2 and brain natriuretic peptide. RESULTS: The plasma fibronectin level in patients with hypertrophic cardiomyopathy was significantly lower in comparison to the healthy subjects [215.5±47.3μg/ml, n=17 vs. 376.7±134.8μg/ml, n=17; p<0.0001]. CONCLUSION: In this study we present and confirm our initial proteomic findings and we suggest fibronectin as a potential indicator of an extracellular matrix remodeling related to the hypertrophic cardiomyopathy.
Keywords: dospělí; Middle Aged; Adult; Fibronectins; lidé; hypertrofická kardiomyopatie; Aged; Humans; senioři; Male; mužské pohlaví; Cardiomyopathy, Hypertrophic; fibronektiny; lidé středního věku; ženské pohlaví; Female